ANALISIS MODEL PEMBELAJARAN KONVENSIONAL DAN MODEL PEMBELAJARAN ISLAM - Huda, Samsul; Mukri, Rusdiono; Isnawati (Prodi PGMI IAI Sahid, 2026)
Conceptual understanding is a key focus that should be considered in the implementation of instruction in elementary schools. The level of elementary students’ conceptual understanding can be measured based on indicators such as interpreting, giving examples, classifying, summarizing, drawing inferences, comparing, and explaining. The use of audiovisual media aims to enhance students’ cognitive abilities by providing stimuli such as moving images and sounds and by delivering messages intended to influence their attitudes and emotions. This study aimed to investigate the effect of implementing audiovisual learning media using Canva to improve second-grade students’ conceptual understanding of addition. The study was conducted at MIS Darul Ihya Ciomas with 34 second-grade students as participants. A quantitative approach employing the Research and Development (R&D) method with the ADDIE development model was used. The research adopted a One-Group Pretest–Posttest Design. Based on the results of the study, the average posttest score of students’ conceptual understanding of addition was 83.03, while the average pretest score was 60.21. The data were analyzed using SPSS 26 for Windows with a Paired Sample T-test at α = 0.001, and the obtained significance value of 0.000 < α = 0.001. These results indicate a significant difference between the posttest and pretest scores. It can therefore be concluded that the use of audiovisual learning media developed with Canva improved the conceptual understanding of addition among second-grade elementary school students in mathematics